Monumenta; 3de biënnale van de Antwerpse galerijen. (Antwerpen : Provinciebestuur, 1987)
Adler, André ; Alechinsky, Pierre ; Ampe, Dominique ; Anderle, Jiri ; Antal, Sandro ; De Backer, Dirk ; Badur, Frank ; Baeyens, Martin R. ; Bandau, Joachim ; Baquié, Richard ; Bas, François Le ; van Bergen, Thé ; Bervoets, Fred ; Van Beveren, Kris ; Beyns, Freddy ; Bijl, Guillaume ; Bilquin, Jean ; Blacker, Kate ; Blocher, Sylvie ; De Blok, Luc ; Boekhout, Henze ; Boisrond, François ; Bolle, Jos ; Bonnal, Daniel ; Bonoli, A. ; Bontinck, Marijke ; Bosman, Ria ; Bouttens, Philippe ; Van Braeckel, Malou ; Braekman, Dirk ; Brams, Maurice ; Brancusi, Constantin ; Brems, Walter ; Broodthaers, Marcel ; Bruna-Hautman, Sigefride ; Bruneau ; Brusselmans, Luc ; Bruyninckx, Rob ; Buren, Daniel ; Byars, James Lee ; Cabrita Reis, Pedro ; Van Caeckenbergh, Patrick ; Callens, Mario R.G. ; Camurati, Delfina ; Cane, Franky ; Carlier, Jan ; Castelyns, Frank J.M.A. ; Citroen, Paul ; De Clerck, Antoon ; Cobbaert, Jan ; Coeckelberghs, Luc ; Cole, Willem ; Colton, Adam ; Copers, Leo ; Corneille ; Cucchi, Enzo ; Van Daele, Nico ; Daems, Walter ; Dahn, Walter ; Daniels, René ; David, Z. Ben ; Debaere, Hugo ; Decq, Bart ; Delbès, Jean-Louis ; Denmark ; Desmet, Eric ; Devos, Danny ; Dieleman, Piet ; Dokoupil, Jiri Georg ; Dries, Jan ; Dyckmans, Bruno ; Eachus, Paul ; Ebbesen, Torben ; Eerdekens, Fred ; Efrat, Benni ; Evers, Winfred ; Fabro, Luciano ; Fainaru, Belu-Simion ; Ferreo, Constantin ; Fierens, Kris ; Florin, Maen ; Folon, Jean-Michel ; Fransen, Tom ; Frohner, Adolf ; Ganzevoort, Wybrand ; Gasteiger, Jakob ; Van Gestel, Fik ; Geysels, Ludo ; Goedhart, Johan ; Goethals, Marc ; Goezu, André ; Goto, John ; Groenen, Jean ; Grossen, Luc ; Grygar, Milan ; Haccuria, Maurice ; Haenen, Toon ; Hambleton, Richard ; Hamersma, Gerlof ; Haring, Keith ; Hauters, Erwin ; etc.
boek